2020
DOI: 10.1093/ibd/izaa033
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Ulcerative Colitis in Japanese Individuals Using Population-specific SNP Array

Abstract: Background To clarify the genetic background of ulcerative colitis (UC) in the Japanese population, we conducted a genome-wide association study (GWAS) using a population-specific single nucleotide polymorphism (SNP) array. Methods We performed a GWAS and replication study including 1676 UC patients and 2381 healthy controls. The probability of colectomy was compared between genotypes of rs117506082, the top hit SNP at HLA lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…We examined the correlation between SNP rs117506082 and clinical outcomes in our cohort. Our previous study showed that SNP rs117506082 at the HLA region was significantly associated with UC in the group with the GA + AA genotype [19]. In contrast, the present study revealed that the AA group had a higher proportion of pancolitis.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…We examined the correlation between SNP rs117506082 and clinical outcomes in our cohort. Our previous study showed that SNP rs117506082 at the HLA region was significantly associated with UC in the group with the GA + AA genotype [19]. In contrast, the present study revealed that the AA group had a higher proportion of pancolitis.…”
Section: Discussioncontrasting
confidence: 66%
“…The top SNP (with the lowest p value) was rs117506082. The G allele of this SNP increases the risk of UC development, whereas the A allele is a reference allele [19]. Furthermore, although the GG genotype of SNP rs117506082 was a risk factor for the onset of UC, the need for surgery in a 30-year follow-up was significantly lower in this genotype than in the GA and AA alleles, suggesting that the GG genotype might have a better clinical outcome.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…There is evidence of population strati cation, such as differences between populations in the genetic factors contributing to UC risk [27,28]. We trained the PRS model on the sample sets containing only Europeans.…”
Section: Population Strati Cationmentioning
confidence: 99%